Predictive Values of Quantitative VS Qualitative Culture of Broncholaveolar Lavage in Diagnosis of Ventilator Associated Pneumonia in Patients on Mechanical Ventilation - Travar, Maja; Kovacevic, Pedja; Golic, Darko (International Journal of Innovative Research in Medical Science, 2019)
Purpose: Ventilator associated pneumonia (VAP) is one of the most common hospital-acquired infection in patients hospitalized in intensive care unit (ICU). Aim of this study was to evaluate predictive values of quantitative and qualitative culture of broncholaveolar lavage (BAL) in the diagnosis of VAP comparing with clinical pulmonary infection score (CPIS), and to determine positive and negative predictive values of the tests in patients on mechanical ventilation. Methodology: 209 samples were prospectively taken from the patients hospitalized in ICU on mechanical ventilation; along with the clinical pulmonary infection score (CPIS). After sampling, quantitative and qualitative culture of BAL was done. As the cut off value of quantitative culture 104 CFU/mL was taken, according CDC recommendations. Results: In our study, sensitivity of the quantitative culture of BAL was 91%, specificity 70%, positive predictive value 80% and negative predictive value was 85%. Sensitivity of the qualitative culture of BAL was 93%, specificity 36%, positive predictive value 70,2% and negative predictive value was 76%. Conclusion: Quantitative culture of BAL has better predictive values in VAP diagnosis in patients on mechanical ventilation, helping in the discrimination between colonization and the infection. Qualitative culture of BAL has higher sensitivity, but lower specificity than quantitative culture.